2011
DOI: 10.1161/circulationaha.111.018028
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Low-Level Vagus Nerve Stimulation Reduces Stellate Ganglion Nerve Activity and Paroxysmal Atrial Tachyarrhythmias in Ambulatory Canines

Abstract: Background We hypothesize that left sided low-level vagus nerve stimulation (LL-VNS) can suppress sympathetic outflow and reduce atrial tachyarrhythmias in ambulatory dogs. Methods and Results We implanted in 12 dogs a neurostimulator to stimulate left cervical vagus nerve and a radiotransmitter for continuous recording of left stellate ganglion nerve activities (SGNA), vagal nerve activities (VNA) and electrocardiograms. Group 1 dogs (N=6) underwent 1 week continuous LL-VNS. Group 2 dogs (N=6) underwent int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
168
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(177 citation statements)
references
References 41 publications
9
168
0
Order By: Relevance
“…One in three patients with paroxysmal AF, and up to 70% of younger patients, present with well-defined adrenergic or vagal triggers 72,73 . Low-level vagal stimulation prevents AF by decreasing sympathetic and parasympathetic cardiac responsiveness in animal models susceptible to AF 74 . High-intensity endurance training is an evolving risk factor underlying AF in middle-aged Europeans without overt structural heart disease 75,76 , which can be mediated by an elevated parasympathetic tone, structural changes, or by changes in ion-channel expression 14,73,77 .…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…One in three patients with paroxysmal AF, and up to 70% of younger patients, present with well-defined adrenergic or vagal triggers 72,73 . Low-level vagal stimulation prevents AF by decreasing sympathetic and parasympathetic cardiac responsiveness in animal models susceptible to AF 74 . High-intensity endurance training is an evolving risk factor underlying AF in middle-aged Europeans without overt structural heart disease 75,76 , which can be mediated by an elevated parasympathetic tone, structural changes, or by changes in ion-channel expression 14,73,77 .…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…A number of animal studies using rats and dogs have shown that chronic VNS improved LV hemodynamics 24,25 and, more importantly, improved survival in HF. 26 With an implanted device to continuously record autonomic nerve activity in ambulatory canines, Shen et al 27 observed that chronic VNS led to a significant reduction in sympathetic activity from the left stellate ganglion, which may underlie the cardioprotective property of VNS. Besides, VNS has additional beneficial effects:…”
Section: Preclinical Researchmentioning
confidence: 99%
“…Despite the fact that vagal stimulation has been used for years as a method to induce AF, recent experimental studies in dogs have demonstrated that low level VNS (below the threshold needed to reduce heart rate) may be antiarrhythmic in the atrium. Shen et al 80 demonstrated that left-sided low-level vagal stimulation decreased left-sided stellate ganglion activity, decreased the incidence of AF and atrial tachycardia, and decreased sympathetic innervation within the stellate ganglion. 80 Similarly, Sha et al, 81 in a study of acute, right-sided, low-level vagal stimulation, found that the threshold to induce AF was higher in the VNS group, and the response of heart rate to direct sympathetic and parasympathetic stimulation was blunted in the setting of low level vagal stimulation.…”
Section: Vagal Stimulation Vagal Stimulation and Atrial Electrophysiomentioning
confidence: 99%
“…Shen et al 80 demonstrated that left-sided low-level vagal stimulation decreased left-sided stellate ganglion activity, decreased the incidence of AF and atrial tachycardia, and decreased sympathetic innervation within the stellate ganglion. 80 Similarly, Sha et al, 81 in a study of acute, right-sided, low-level vagal stimulation, found that the threshold to induce AF was higher in the VNS group, and the response of heart rate to direct sympathetic and parasympathetic stimulation was blunted in the setting of low level vagal stimulation. In addition, neural activity in a ganglion of the intrinsic cardiac nervous system was reduced with low level VNS, which may be the basis for its antiarrhythmic effect.…”
Section: Vagal Stimulation Vagal Stimulation and Atrial Electrophysiomentioning
confidence: 99%
See 1 more Smart Citation